IgG4-Related Disease of the Ovary - Sevda AKYOL; Fatma ÖZ ATALAY; Secil HASDEMIR; Ömer YERCI (Federation of Turkish Pathology Societies, 2021)
Immunoglobulin G4-related disease is characterized by dense fibrosis, obliterative phlebitis, and lymphoplasmacytic infiltration that contains abundant IgG4 positive plasma cells. It causes tumefactive lesions in the involved organs and is most commonly seen in the salivary glands, pancreas, and retroperitoneum. Ovarian involvement has been reported in only two cases. In our case, a 58-year-old female patient presented with abdominal distention and pain. Pelvic computed tomography revealed a soft tissue lesion compatible with the omental cake, several intraabdominal implants, and bilateral adnexal fullness. A laparotomy was performed under suspicion of peritoneal carcinomatosis secondary to bilateral adnexal mass. In the histopathologic examination, abundant lymphoplasmacytic infiltration and dense fibrosis were observed in both ovaries and the peritoneum. In the areas of greatest density, the density of IgG4-positive plasma cells was found to range from 40 to 50 per high-power field. The patient was accepted as suffering from probable IgG4-related disease because of the bilateral involvement of the ovaries and the histopathological findings. In conclusion, we present this case to draw attention to the fact that IgG4-related disease can also be seen in the ovary.